2008
DOI: 10.1111/j.1523-1739.2008.00932.x
|View full text |Cite
|
Sign up to set email alerts
|

Determining Optimal Population Monitoring for Rare Butterflies

Abstract: Determining population viability of rare insects depends on precise, unbiased estimates of population size and other demographic parameters. We used data on the endangered St. Francis' satyr butterfly (Neonympha mitchellii francisci) to evaluate 2 approaches (mark-recapture and transect counts) for population analysis of rare butterflies. Mark-recapture analysis provided by far the greatest amount of demographic information, including estimates (and standard errors) of population size, detection, survival, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
88
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(92 citation statements)
references
References 30 publications
4
88
0
Order By: Relevance
“…This approach adds a geographic dimension to the monitoring schemes for endangered butterfly species proposed by Haddad et al (2008) and Nowicki et al (2008). Haddad et al (2008) presented techniques to determine population parameters for the purpose of undertaking population viability analysis and concluded that a combination of transect and mark-recapture sampling would generate the most accurate results at least cost and harm to the butterflies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach adds a geographic dimension to the monitoring schemes for endangered butterfly species proposed by Haddad et al (2008) and Nowicki et al (2008). Haddad et al (2008) presented techniques to determine population parameters for the purpose of undertaking population viability analysis and concluded that a combination of transect and mark-recapture sampling would generate the most accurate results at least cost and harm to the butterflies.…”
Section: Discussionmentioning
confidence: 99%
“…Haddad et al (2008) presented techniques to determine population parameters for the purpose of undertaking population viability analysis and concluded that a combination of transect and mark-recapture sampling would generate the most accurate results at least cost and harm to the butterflies. Nowicki et al (2008) addressed efforts to define butterfly distribution and concluded that they must be improved by incorporation of statistical correctors for detectability (MacKenzie et al 2002(MacKenzie et al , 2003.…”
Section: Discussionmentioning
confidence: 99%
“…in Leopold and Fartmann 2005). However, it is important to note that transect counts generate indices of relative abundance but not precise estimates of population densities, though transect count data can be correlated with population size, sometimes to a high degree (Haddad et al 2008, Nowicki et al 2008. Among others, differing detection probability by species, observer, region, year and season can bias the data recorded (e.g., Kery and Plattner 2007).…”
Section: Monitoring Day-active Lepidopteramentioning
confidence: 99%
“…by distance sampling (see below); some freeware programs such as MARK or PRESENCE might also be helpful in this respect. However, mark-release-recapture (MRR) methods are most often used to calculate detection probabilities for species as well as estimates of population sizes and survival probabilities (e.g., Haddad et al 2008). Yet, MRR methods are quite laborious, may not be adequate for highly mobile species with low recapture rates, and are potentially harming the marked individuals or changing their behaviour (Sutherland 2006).…”
Section: Monitoring Day-active Lepidopteramentioning
confidence: 99%
“…Capture-mark-recapture methods such as those employed by 363 Calvert (2004), but replicated over years and locations, seem to offer the most promising means 364 of accomplishing this goal of improved overwinter density estimation. Capture-mark-recapture is 365 the most common method for estimating population size in butterflies (e.g., Gall, 1984; 366 Bergman, 2001;Baguette & Schtickzelle, 2003;Haddad et al, 2008), and its systematic use in 367 the high-elevation Oyamel fir forests of central Mexico would enable robust estimates of daily 368 and total overwintering population sizes, as well as survival and emigration probability 369 (Williams et al, 2002). However, capture-mark-recapture methods come at the considerable cost 370 of disturbing overwintering individuals, a practice that is currently disallowed and arguably not 371 prudent given the small population size and the negative impacts of disturbance.…”
mentioning
confidence: 99%